Assessing carbon emissions of facility agriculture involving photovoltaic greenhouses – insights from table grapes cultivation - Yichun Li; Shuyue Li; Yaru Luo; Xuecai Wang; Hengcheng Zhang; Yuquan W. Zhang; Shiren Song (Carbon Neutrality)
Abstract Taking climate actions is of increasing importance. The agricultural sector is exploring its carbon neutrality transition pathway. Current relevant studies paid limited attention to agricultural products such as table grapes. This study takes table grapes cultivation in Shanghai as a case study, employing the life cycle assessment (LCA) to account for the carbon emissions and environmental impacts of five different conditions, including open field, simple greenhouse, continuous greenhouse, continuous greenhouse with photovoltaic power, and improved continuous greenhouse with photovoltaic power. Utilizing both observation and simulation data, the SimaPro software is applied to analyze the LCA carbon and environmental footprints of table grapes cultivation. The results show that simple greenhouse grapes exhibit the lowest level of carbon emissions (452 kgCO2-eq/mu-year), and meanwhile the most economical. Moreover, improved greenhouse utilizing photovoltaic power (1.26 × 103kgCO2-eq/mu-year) exhibits higher carbon emissions, however with lower levels of environmental toxicity due to utilizing grapevines for organic fertilizers. Thus, simple greenhouse grapes would score best if considering carbon emissions only, while the improved greenhouse model holds greater potential as a form of modernized facility-based agriculture. Furthermore, this study suggests that for the broader facility agriculture, using low carbon structure materials would serve as the level to reduce carbon footprints.